Arab linguistics : an introductory classical text with translation and notes - Shirbīnī, Muḥammad ibn Aḥmad, -1570 (Amsterdam studies in the theory and history of linguistic science. Studies in the history of linguistics, 1981)
This volume provides an analysis of a famous medieval Arabic grammatical text, al-Ajurrumiya (c. 1300), as commented on by aš-Šhirbini (d. 1570). This edition includes the original text and a translation into English, as well as extensive comments and annotations, with the aim of making accessible both to Arabists and non-Arabists the main elements of indigenous Arabic linguistics, and thereby at least partially filling a large blank in the history of linguistics.